2020
DOI: 10.1016/j.meegid.2020.104556
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-species nature and differential gene expression of severe acute respiratory syndrome coronavirus 2 and phylogenetic analysis of a novel Iranian strain

Abstract: A novel coronavirus related to severe acute respiratory syndrome virus, (SARS-CoV-2) is the causal agent of the COVID-19 pandemic. Despite the genetic mutations across the SARS-CoV-2 genome being recently investigated, its transcriptomic genetic polymorphisms at inter-host level and the viral gene expression level based on each Open Reading Frame (ORF) remains unclear. Using available High Throughput Sequencing (HTS) data and based on SARS-CoV-2 infected human transcriptomic data, this study presents a high-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…It is currently well-established that intrahost SARS-CoV-2 variability is frequent across the viral genome in COVID-19 patients ( 79 81 ). It was also reported that intrahost SARS-CoV-2 variability is higher in cancer patients compared to non-cancer counterparts ( 82 ).…”
Section: Tissue-specific Patterns Of Sars-cov-2 Variantsmentioning
confidence: 99%
“…It is currently well-established that intrahost SARS-CoV-2 variability is frequent across the viral genome in COVID-19 patients ( 79 81 ). It was also reported that intrahost SARS-CoV-2 variability is higher in cancer patients compared to non-cancer counterparts ( 82 ).…”
Section: Tissue-specific Patterns Of Sars-cov-2 Variantsmentioning
confidence: 99%
“…The mutations (g.a28271-, and g.gat28280cta) alter the Kozak sites of N and ORF9b, and may influence the translational efficiency of the two genes. Protein N has the highest translation rate(24,25) and its expression is associated with the replication of the genomic RNA(26). The product of ORF9b has an interferon (IFN) antagonistic activity and can suppress the IFN production(27).…”
mentioning
confidence: 99%
“…Particularly, single nucleotide polymorphisms (SNP) profiles reveal that ORFs that codify for RdRp and S proteins, ORF8, and NP of SARS-CoV-2 have suffered mutations at the host level, evidencing a key point for changes related to transmissibility and virulence. Using high-throughput sequencing (HTS) and transcriptomics data from studies in humans infected with SARS-CoV-2, Ghorbani et al [ 29 ], defined a high-resolution map of the SNP hot spots of the SARS-CoV-2 in a viral population at the inter-host level showing that at least 22 sites have significant differences in mapped readings suggesting potential RNA modifications. The positions of the SNPs in the coding regions of the SARS-CoV-2 ORFs were located in RdRp ORF (14 SNP), S ORF (4 SNP), ORF8 (2 SNP), and N ORF (1 SNP).…”
Section: Resultsmentioning
confidence: 99%
“…More studies are needed to compare enough virus sequences from different geographic locations to better understand the intra-host behavior and selection pressure. The amount of modifications at NSP8 suggests that this could affect its replication rate and if crossing of the host barrier is allowed, its replication would be faster and more efficient [ 7 , 19 , 29 , 30 ]. It is reported that some of the most representative homoplasies in the genome of this virus are found at site 11.083 which comprises a region of ORF1a that encodes the non-structural protein Nsp6, and at site 21.575 that corresponds to the spike protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation